Development of Android-Based Class in Hole Teaching Materials to Increase Students' History Awareness - Nastiti Mufidah; Khoirun Nikmah; Tiksna Apta Samoda; Faninda Novika Pertiwi (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
Teaching materials are an important point in the implementation of student lectures in class. The availability of printed teaching materials is very unattractive in this modern era. This research aims to develop teaching materials for the Android-based Classical Indonesian History course. Research using ADDIE. Data collection techniques through pre-test and post-test for Tadris IPS students. The data analysis technique in this research went through three stages, namely expert validity test, normality test and paired sample t-Test. Android-based Classic Indonesian History with Mobile Learning (Class In Hole) teaching materials to increase students' historical awareness have an effect on increasing students' understanding of concepts based on the results of the "Paired Samples Test", it is known that the t count has a negative value of -18.979. This negative T value causes the average pre-test score to be lower than the average post-test score. Next is the stage of finding the t table value, where the t table is searched based on the df (degree of freedom) value and significance value. From the output above, it is known that the df is 60 and the significance is 0.05. Based on the number of student participants of 61 and an error significance level value of 5%, the t table value is 2.00. So it can be concluded that the calculated t value (18.979) > t table (2.00). It can be concluded that the use of Class In Hole teaching materials to increase students' historical awareness has a significant effect. Class In Hole is suitable to be given as teaching material to students.Keywords: Teaching materials, class in hole, historical awareness.